Representações sociais de familiares de pacientes internados no CTI sobre o processo saúde doença e suas implicações para o cuidado de si - FREITAS, Karina de Oliveira (2019)
This research has as object of study the social representations of family members of patients in the ICU on the health-disease process and its implications for the care of itself. For this guide, we drew the following questions: What are the representations of family members of patients in the ICU on the health condition? What is the implication of these representations for the care of you? To answer the questions the following objectives were defined: Identify and describe the representations of family members of patients in the ICU on the health-disease process and analyze the implications of these representations for the care of itself. This research was descriptive exploratory with a qualitative approach, adopting the theory of social representations as a theoretical and conceptual support, according to Serge Moscovici and Denise Jodelet. Data collection was conducted through semi-structured interview technique with open questions. The same technique was added to a questionnaire to identify the sociocultural profile of family members who stepped into the ICU of Belém do Pará HUJBB until data saturation. Among the various content analysis techniques, it was decided to use the Bardin technique. This is divided into three main phases: pre-analysis, material exploration and treatment of results. Through this analysis emerged three main themes: Health and Disease: a vital balance; ICU: Death Care and x; The care in the social representations of the health-disease process. With that establishes the importance of understanding family of representations of patients admitted to the ICU on the health - disease process in order to identify psychosocial problems that will interfere with the adaptation of family and social life of these individuals, who may be worked by the multidisciplinary team so as to improve the perception of family members, to the situation in which they find themselves.